Politik dalam Pendidikan Vernakular Cina di Semenanjung Malaysia: Satu Perspektif Hubungan Etnik Majoriti-Minoriti - Tan , Yaosua (Penerbit Universiti Sains Malaysia, 1998)
This paper attempts to provide a theoretical framework to conceptualize the intense ethnic assertions in the politics of Chinese vernacular education in Peninsular Malaysia from the perspective of majority-minority ethnic relations in a multi-ethnic society. It examines four educational policies, namely, Razak Report, 1956, Education Ordinance, 1957, Rahman Talib Report, 1960 and Education Act, 1961. It posits the notion that inherent in the phenomenon of majority-minority ethnic relations is the manifestation of ethnic dominationsubordination.